Long-term adherence to direct acting oral anticoagulants and the influence of health beliefs after switching from vitamin-K antagonists: Findings from the Switching Study. Issue 208 (December 2021) - Bartoli-Abdou, John K.; Patel, Jignesh P.; Vadher, Bipin; Brown, Alison; Roberts, Lara N.; Patel, Raj K.; Arya, Roopen; Auyeung, Vivian
Abstract: Aims: Switching non-adherent patients prescribed anticoagulant treatment to a regime with less monitoring could lead to significant non-adherence. Health beliefs are known to influence medication adherence; however, the extent of this influence is unknown in patients switched from vitamin-K antagonists (VKAs) to direct oral anticoagulants (DOACs). This study aimed to determine adherence to long-term therapy in patients switched from VKAs to DOAC due to low time in therapeutic range (TTR) and if adherence is associated with health beliefs. Methods: The Switching Study is a longitudinal observational cohort study following patients for at least 1-year. 254 patients anticoagulated with VKAs for stroke prevention in atrial fibrillation (AF) or secondary prevention of venous thromboembolism (VTE) and TTR < 50% were recruited from anticoagulation clinics at King's College Hospital, London, UK. All participants were switched to DOAC and had health beliefs measured at baseline with VKA, 1-month and 12-months after switching. Results: Of the 220 patients who completed 12-month follow-up 39% had sub-optimal adherence measured by self-report. 23% were non-adherent according to prescriptions issued. Increasing concerns about anticoagulation over time relative to beliefs about necessity was associated with lower self-reported adherence (OR = 0.902 95%C.I: 0.836, 0.974; p  = 0.008). At baseline, believing that medications in general were overused in healthcare was negatively associated with adherence to DOAC (β = −1.5, 95%C.I: −2.7, −0.3; p  = 0.013). Conclusions: Although many patients who switched were adherent to therapy long-term, between 23 and 39% of patients exhibited sub-optimal adherence: these patients can be identified through their modifiable health beliefs at the time of switching. Highlights: Adherence to DOAC therapy in up to one-third of patients is sub-optimal. Patient's health beliefs can predict non-adherence and offer a modifiable target for clinicians in their consultations. Increasing concerns about anticoagulation relative to beliefs about necessity are associated with lower rates of adherence. Interventions targeting treatment and health beliefs should be tested, particularly with the growing use of DOAC therapy.